Genetic heterogeneity in Pakistani microcephaly families. (7th August 2012) - Sajid Hussain, M; Marriam Bakhtiar, S; Farooq, M; Anjum, I; Janzen, E; Reza Toliat, M; Eiberg, H; Kjaer, KW; Tommerup, N; Noegel, AA; Nürnberg, P; Baig, SM; et al.
Abstract : Autosomal recessive primary microcephaly (MCPH) is caused by mutations in at least eight different genes involved either in cell division or DNA repair. Most mutations are identified in consanguine families from Pakistan, Iran and India. To further assess their genetic heterogeneity and mutational spectra, we have analyzed 57 consanguine Pakistani MCPH families. In 34 MCPH families, we detected linkage to five out of the eight well‐characterized disease loci and identified mutations in 27 families, leaving seven families without mutations in the coding exons of the presumably underlying MCPH genes. In the MCPH cohort 23 families could not be linked to any of the known loci, pointing to remarkable locus heterogeneity. The majority of mutations were found in ASPM followed by WDR62, CENPJ, CEP152 and MCPH1 . One ASPM mutation (p.Trp1326*) was found in as many as eight families suggesting a Pakistani founder mutation. One third of the families were linked to ASPM followed by WDR62 confirming previous data. We identified three novel ASPM mutations, four novel WDR62 mutations, one novel MCPH1 mutation and two novel CEP152 mutations. CEP152 mutations have not been described before in the Pakistani population.